Allegheny woodrat occupancy across western Virginia, United States. Issue 3 (23rd March 2022) - Lombardi, Jason V.; Mengak, Michael T.; Castleberry, Steven B.
Abstract : The Allegheny woodrat Neotoma magister, a rock outcrop habitat specialist, has suffered drastic reductions in geographic range over the past 40 years. Previous research has examined habitat characteristics at varying spatial scales, but none have used occupancy modeling to examine trends over time. Therefore, we used presence/absence data from live trapping to assess environmental variables likely to influence Allegheny woodrat occupancy and detection patterns at a regional scale across western Virginia, USA, from 2009 to 2011. We observed a shift in occupancy and detection rates across years with a peak in 2009, a decline in 2010 and apparent recovery in 2011. We found significant isolation by distance effect influencing woodrat occupancy across the region, with occupancy linked to sites in closer proximity to other occupied locations. Occupancy increased in oak and hickory forests, suggesting woodrat occurrence increases in forest types with a higher abundance of hard and soft mast‐producing species. We found variable effects of elevation over time, with higher occupancy at higher elevations in 2009 but at lower elevations in 2010, which may be explained by variation in winter severity and mast abundance across years. Allegheny woodrat management should include activities to promote and retain mast‐producing species at higher elevations to offset potential subpopulation contractions during harsh winters.